2016
DOI: 10.18632/oncotarget.10584
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B exerts anti-cancer activities in human multiple myeloma cellsin vitroandin vivoby modulating multiple cellular pathways

Abstract: Cucurbitacin B (CuB), a triterpenoid compound isolated from the stems of Cucumis melo, has long been used to treat hepatitis and hepatoma in China. Although its remarkable anti-cancer activities have been reported, the mechanism by which it achieves this therapeutic activity remains unclear. This study was designed to investigate the molecular mechanisms by which CuB inhibits cancer cell proliferation. Our results indicate that CuB is a novel inhibitor of Aurora A in multiple myeloma (MM) cells, arresting cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…Cucurbitacins exhibit various biological and pharmacological activities, including antitumor, anti-inflammatory, hepatoprotective, and cytotoxic effects [ 18 20 ]. Particularly, most cucurbitacins, such as A, B, E, and I, affect the growth of various human cancer cell lines including breast, prostate, and brain cancer cells [ 21 23 ]. In addition, recent study also demonstrated that cucurbitacin B and I exert the preventive effects of adipocyte differentiation by modulating STAT3 signaling pathway [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cucurbitacins exhibit various biological and pharmacological activities, including antitumor, anti-inflammatory, hepatoprotective, and cytotoxic effects [ 18 20 ]. Particularly, most cucurbitacins, such as A, B, E, and I, affect the growth of various human cancer cell lines including breast, prostate, and brain cancer cells [ 21 23 ]. In addition, recent study also demonstrated that cucurbitacin B and I exert the preventive effects of adipocyte differentiation by modulating STAT3 signaling pathway [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cell lysates from SupM2, an ALK-positive anaplastic large cell lymphoma cell line known to have a high pSTAT3 expression [ 29 ], were used as the positive control. To explore the possible activators of STAT3 in 3D culture, we checked the expression level of several cytokines which are known to induce STAT3 phosphorylation in MM: IL6, IL21 and IL10 [ 30 , 31 , 32 ]. As shown in Figure S3 , the expression of all three cytokines in U266 cells increased by 1.5–2.5 folds after 1 day of 3D culture compared to cells in conventional culture.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the CuB-induced suppression of cell proliferation is associated with cofilin activation (dephosphorylation) ( Yang et al, 2017 ). Thus, we investigated the effect of CuE on Caco-2 cell proliferation.…”
Section: Resultsmentioning
confidence: 99%